Bioresorbable composite polymeric materials for tissue engineering applications. Issue 13 (2nd September 2021) - Hajebi, Sakineh; Mohammadi Nasr, SAeed; Rabiee, Navid; Bagherzadeh, Mojtaba; Ahmadi, Sepideh; Rabiee, Mohammad; Tahriri, Mohammadreza; Tayebi, Lobat; Hamblin, Michael R.
Abstract: This review covers the development of bioresorbable polymeric composites for applications in tissue engineering. Various commercially available bioresobable polymers are described, with emphasis on recent bioresorbable composites based on natural and synthetic polymers. Bioresorbable polymers contain hydrolyzable bonds, which are subjected to chemical degradation via either reactive hydrolysis or enzyme-catalyzed active hydrolysis. For synthetic polymers, chemical hydrolysis is the most important mode of degradation. The degradation rate can be controlled by varying the molecular weight and crystallinity. Examples of bioresorbable polymers are: polyurethane, poly(D, L)lactide, poly(lactic-co-glycolic) acid, poly(α-hydroxy acids), cross-linked polyester hydrogels, poly(orthoesters), polyanhydrides and polyethylene glycol. Graphical Abstract: UF0001